2022
DOI: 10.1038/s41467-022-34053-7
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Hi-C with short and long-read genome sequencing reveals the structure of germline rearranged genomes

Abstract: Structural variants are a common cause of disease and contribute to a large extent to inter-individual variability, but their detection and interpretation remain a challenge. Here, we investigate 11 individuals with complex genomic rearrangements including germline chromothripsis by combining short- and long-read genome sequencing (GS) with Hi-C. Large-scale genomic rearrangements are identified in Hi-C interaction maps, allowing for an independent assessment of breakpoint calls derived from the GS methods, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…However, the general applicability of this concept remains under investigation, as disruption of TADs and enhancer-promoter interactions are not always accompanied by changes in expression. Studies in Drosophila 7 and in human congenital chromothrypsis cases 8 indicate indeed a degree of robustness of the genome against such events.…”
mentioning
confidence: 99%
“…However, the general applicability of this concept remains under investigation, as disruption of TADs and enhancer-promoter interactions are not always accompanied by changes in expression. Studies in Drosophila 7 and in human congenital chromothrypsis cases 8 indicate indeed a degree of robustness of the genome against such events.…”
mentioning
confidence: 99%
“…This study reported that while the majority of breakpoints reshuffle TADs, most genes located 200‐kb around a breakpoint do not show significant expression changes. [ 109 ] These data suggest that the enhancer adoption mechanism may be a rare cause of disease.…”
Section: D Genome Organizationmentioning
confidence: 99%
“…Alternatively, the umbrella term “chromoanagenesis” can be used to encompass a spectrum of complex SVs resulting in rearranged derivative chromosomes. Long-read and Hi-C data of germline genomes also support this diversity of rearrangements and categorization into chromothripsis-like and chromoplexy-like patterns [10]. Chromothripsis is characterized by DNA shattering and haphazard repair in which genomic fragments are randomly joined, resulting in many interleaved SVs and an oscillating CN pattern with losses [11].…”
Section: Introductionmentioning
confidence: 99%
“…It can result in fusion genes such as EWSR1::FLI1 and is thought to arise when DNA damage occurs during co-localization of chromosomes in transcription hubs [1]. Both chromothripsis and chromoplexy can result in derivative chromosomes, differing mainly in the presence or absence of large copy number changes [10, 12].…”
Section: Introductionmentioning
confidence: 99%